Effect of Leachate Blending on Anaerobic Digestion of Organic Fraction of Municipal Solid Waste - Nair, Arjun (Université d'Ottawa / University of Ottawa, 2013)
Anaerobic digestion of the Organic Fraction of Municipal Solid Waste (OFMSW) generates a mixture of methane (CH4), carbon dioxide (CO2) and water (H2O). Beyond the field capacity the water generated is collected and recirculated as leachate in Bioreactor Landfills (BLs.) Leachate recirculation has a profound advantage on biodegradation of the Organic Fraction of Municipal Solid Waste (OFMSW) in the landfills. Mature leachate from older sections of landfills (>20 years) and young leachate were blended prior to recirculation in the ratios 3/3 mature, 3/3 young, 1/3 mature-2/3 young and 2/3 old-1/3 young and their effect on biodegradation and biogas production monitored. In addition to analysis of the effect of blending old and new leachates, the study also analyses the effect of an open vs. a closed recirculation loop and the effect of organic loading rates of OFMSW in landfills. Data collected from initial batch tests supplement column bioreactors simulating bioreactor landfills with real world OFMSW from operational landfill facilities in Ontario, Canada. The results are conclusive that the biogas generation can be improved by up to 92% by blending the leachate in an open loop recirculation system as compared to a conventional closed loop system employed in landfills today.
Keywords: Leachate; leachate recirculation; leachate blending; leachate treatment; bioreactor landfill; municipal solid waste; mature leachate; anaerobic biodegradation; solid waste